Spred2-deficiecy Protects Mice from Polymicrobial Septic Peritonitis by Enhancing Inflammation and Bacterial Clearance. Issue 1 (December 2017) - Itakura, Junya; Sato, Miwa; Ito, Toshihiro; Mino, Megumi; Fushimi, Soichiro; Takahashi, Sakuma; Yoshimura, Teizo; Matsukawa, Akihiro
Abstract Sepsis is an infection-induced systemic inflammatory syndrome and a major cause of death for critically ill patients. Here, we examined whether the absence of Sprouty-related EVH1-domain-containing protein 2 (Spred2), a negative regulator of the Ras/Raf/ERK/MAPK pathway, influences host defense against polymicrobial sepsis (PMS) induced by cecal ligation and puncture (CLP). Compared to wild-type mice, Spred2−/− mice exhibited higher survival rates with increased level of leukocyte infiltration and local chemokine production and reduced plasma and peritoneal bacterial loads after CLP. The MEK inhibitor U0126 significantly reduced LPS-induced chemokine production by Spred2−/− resident macrophagesin vitro, and decreased CLP-induced leukocyte infiltrationin vivo . Spred2−/− resident macrophages, but not neutrophils or elicited macrophages, exhibited increased phagocytic activity. Interestingly, surface expression of complement receptor 1/2 (CR1/2) was increased in Spred2−/− resident macrophages in response to lipopolysaccharide in a manner dependent on the ERK/MAPK pathway, and blocking CR1/2in vivo resulted in reduced leukocyte infiltration and increased bacterial loads after CLP. Taken together, our results indicate that Spred2-deficiency protects mice from PMS via increased activation of the ERK/MAPK pathway and subsequent increase in innate immune responses. Thus, inhibiting Spred2 may present a novel means to prevent the development of PMS.